Association between cardiorespiratory fitness and handgrip strength with age-related macular degeneration: a population-based study. Issue 8 (28th August 2020) - Katsimpris, Andreas; Jürgens, Clemens; Lüdtke, Lisa; Martin, Bahls; Ittermann, Till; Gläser, Sven; Dörr, Marcus; Ewert, Ralf; Volaklis, Konstantinos; Felix, Stephan B.; Tost, Frank; Völzke, Henry; et al.
Abstract : Aim: To assess whether cardiorespiratory fitness (CRF) and handgrip strength, two objective markers of physical fitness, are associated with age-related macular degeneration (AMD). Methods: We analysed cross-sectional data from the population-based Study of Health in Pomerania (2008–2012) including 1173 adult men and women aged 20–79 years. Fundus photography of the central retina was recorded with a non-mydriatic camera, and images were graded according to an established clinical AMD classification scale by an experienced reader. CRF was measured using peak oxygen uptake (peakVO2 ), oxygen uptake at the anaerobic threshold (VO2 @AT), and maximum power output (Wmax ) from standardised cardiopulmonary exercise testing on a bicycle ergometer according to a modified Jones protocol. Handgrip strength was assessed using a handheld dynamometer. Adjusted prevalence ratios (PR) for the associations of peakVO2, VO2 @AT, Wmax and handgrip strength with AMD were derived from multivariable Poisson regression models. Results: PeakVO2, VO2 @AT, Wmax and handgrip strength were not associated with AMD. Adjusted PR for AMD associated with a 1-SD increment in peakVO2, VO2 @AT, Wmax and handgrip strength were 1.05 (95% CI 0.82 to 1.34), 0.96 (95% CI 0.78 to 1.18), 1.10 (95% CI 0.86 to 1.41) and 1.01 (95% CI 0.79 to 1.30), respectively. These associations were not modified by age, sex, smoking, body mass index and diabetes. Estimates in sensitivity analysis for confounding, selection bias and missing data were similar. Conclusion: In our study, CRF and handgrip strength were not associated with AMD. Nevertheless, longitudinal studies with bigger sample sizes are needed to furtherly examine these associations.